Prospects of nanostructure-based electrochemical sensors for drug detection: a review. Issue 2 (22nd December 2022) - Chaudhary, Manika; Kumar, Ashwani; Devi, Arti; Singh, Beer Pal; Malhotra, Bansi D.; Singhal, Kushagr; Shukla, Sangeeta; Ponnada, Srikanth; Sharma, Rakesh K.; Vega-Olivencia, Carmen A.; Tyagi, Shrestha; Singhal, Rahul
Abstract : The present study represents the advancements achieved over the past ten years towards the development of electrochemical sensors based on nanomaterials. Abstract : The present study represents the advancements achieved over the past ten years towards the development of electrochemical sensors based on nanomaterials. The versatility, sensitivity, selectivity, and capability of analyzing samples with minimal to no pre-treatment means that electrochemical sensors are an attractive and powerful tool for detecting some analgesic and antipyretic drugs such as acetaminophen (AP), ibuprofen (IB), aspirin (ASP), and diclofenac (DCF). These analgesic and antipyretic drugs are very popular as minor pain and fever medications. Controlled doses of these drugs do not harm the human body, but higher concentrations can be hazardous for humans. These drugs are also considered to be emerging chemical pollutants in the environment. Reliable and powerful analytical techniques are thus necessary for the detection of these drugs, for the quality control of pharmaceuticals as well as for environmental control. This review emphasizes the synthesis of nanostructured materials and their use in the electrochemical sensing of analgesic and antipyretic drugs.